Our child is dying: exploring the experiences, challenges and coping mechanisms of Malaysian parents as caregivers of a child with cancer - Ibrahim, Hasniza; Razak, Marini; Aman, Azlina; Sheikh Ahmad, Ismail (University of Malaya, 2019)
Parents as caregivers to paediatric cancer patients face various challenges. This paper highlights the characteristics, caregiving tasks, resources, and other role demands/stressors experienced by a pair of parents as primary family caregivers of a child with cancer in the Malaysian setting. Besides, coping strategies are also put forward as a significant element in understanding the functions of a parent as a caregiver. Hence, this study aims to explore the in-depth experiences of caregivers and investigate the challenges as well as the coping strategies adopted by them, particularly as Muslims. Eight (8) main themes emerged from the findings: (i) chronology; (ii) caregiver roles; (iii) routine changes; (iv) making decisions; (v) financial; (vi) letting go; (vii) external support; and (viii) internal support. This study is unique because the patient was an only child, and he managed to score excellent grades in all subjects in the Malaysian Primary School Achievement Test (UPSR) despite not attending school for almost one year due to cancer treatments.